Preparation method of semi-solid lithium battery
By using fibrosis and rolling technology in semi-solid lithium batteries, the adhesion between the electrode sheet and the current collector is improved, and the problem of low adhesion of the electrode sheet in the prior art is solved, and the circulation performance and safety of the battery are improved, so as to achieve More efficient electrolyte use and lower production costs.
Patent Information
- Application Number
- CN202411342222.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The pole plate and current collector of existing semi-solid lithium batteries have low adhesion to the pole plate, resulting in electrolyte consumption and pole plate falling off during multiple charge and discharge, affecting the cycling performance and safety of the battery.
By mixing the positive and negative electrode active materials with conductive agents, binders and additives at high speed, shearing fibrosis, and adding electrolyte after insulation at a specific temperature, wet balls or dough are formed, and rolling reduction is performed by rolling machine Thin and fit, prepare semi-solid electrode sheets to improve adhesion between the electrode sheets and the current collector.
It significantly improves the circulation performance of semi-solid lithium batteries, enhances the adhesion between the electrode sheet and the current collector, reduces the consumption of electrolyte, avoids the electrode sheet falling off, reduces production costs, and solves the problem of uneven distribution of electrolyte .
Smart Images

Figure CN119208746A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a semi-solid lithium battery. Background Art
[0002] High-performance energy storage technology is essential for the expansion and deployment of renewable energy and solutions to energy problems. Lithium slurry batteries are promising candidates in the field of energy storage, combining the high energy density of conventional lithium-ion batteries with the mutual energy and power energy independence of redox flow batteries, with higher voltage than redox flow batteries and large-scale application. However, due to the high content of highly flammable electrolyte in the slurry of 70wt%–95wt%, there is a certain fire risk.
[0003] Solid-state batteries can significantly improve battery safety and break the energy density bottleneck of liquid batteries. Solid-state batteries use solid electrolytes to partially or completely replace liquid electrolytes, but insufficient electrode-electrolyte surface contact limits their stability and electrochemical performance. As a compromise strategy, in-situ solidification of electrolytes is proposed to manufacture semi-solid-state batteries. Monomers and initiators are introduced into the electrolyte, and a polymer framework is formed by in-situ curing induced by heat. However, the amount of electrolyte solidification cannot be analyzed in this process, and there are problems such as uneven distribution during the curing process.
[0004] Existing semi-solid batteries already have such preparation processes. For example, patent CN 117691202A discloses a low-cost lithium battery manufacturing method, in which the negative electrode mixture after fiberization is prepared into a negative electrode dry electrode. The electrolyte is added to the positive electrode mixture after fiberization and mixed to obtain a semi-dry electrode, which is assembled into a lithium battery with the negative electrode dry electrode. In this invention, the positive electrode semi-dry electrode and the negative electrode dry electrode are not injected with liquid after assembling the battery, and the interface contact between the positive and negative electrodes is poor. In patent CN 117691202A, the fiberized positive and negative electrode materials are all prepared with a semi-solid process to prepare self-supporting pole pieces, which are directly assembled with the positive and negative current collectors and packaged for the battery. In this invention, the adhesion between the self-supporting pole piece and the current collector is low, and the electrolyte is continuously consumed during multiple charge and discharge processes, and the self-supporting pole piece will fall off. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention proposes a method for preparing a semi-solid lithium battery, which can optimize the electrode structure, effectively solve the problem of low adhesion between the electrode and the current collector, improve the cycle performance, further reduce the production cost, and facilitate industrial scale-up.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solution: The present invention discloses a semi-solid lithium battery preparation and electrode structure optimization, comprising the following steps:
[0007] (1) The positive electrode active material, the conductive agent, the binder, and the additive are mixed and sheared at high speed to obtain a fiberized positive electrode material after fiberization; the negative electrode active material, the conductive agent, the binder, and the additive are mixed and sheared at high speed to obtain a fiberized negative electrode material, and the mixture is kept warm at a specific temperature.
[0008] (2) adding an electrolyte to the heat-insulated positive electrode active material and mixing the mixture, and preparing the mixture into wet pellets or dough in a degassing machine to obtain a wet positive electrode mixture; adding an electrolyte to the heat-insulated negative electrode active material and mixing the mixture, and preparing the mixture into wet pellets or dough in a degassing machine to obtain a wet negative electrode mixture;
[0009] (3) placing the wet positive electrode mixture on the current collector, adding a layer of separator, rolling it with a roller machine, adjusting the roller gap to continuously reduce the thickness to the ideal thickness, and laminating it with the positive electrode current collector and rolling it again to obtain a semi-solid positive electrode sheet;
[0010] (4) placing the wet negative electrode block mixture on the separator, rolling it with a roller machine, adjusting the thickness by adjusting the roller gap, laminating it with the negative electrode current collector and rolling it again to obtain a semi-solid negative electrode sheet;
[0011] (5) Assemble the prepared positive and negative electrode sheets to prepare a battery.
[0012] Furthermore, when the step (1) uses a double planetary mixer to perform high-speed shear fiberization, the parameters are set to first stir at a low speed of 1000rpm-1200rpm for 5-10min, then stir at a high speed of 1600rpm-2000rpm for 5-10min, and repeat the cycle three times. The total mixing time is 30min-60min.
[0013] Furthermore, the positive and negative electrode materials after fiberization in step (1) are granular, and a small amount of filaments can be seen.
[0014] Furthermore, the temperature during the mixing process in step (1) should be between 25°C and 30°C.
[0015] Furthermore, the specific temperature of the insulation in step (1) is 40° C.-100° C. to ensure complete fiberization of the PTFE.
[0016] Furthermore, in step (1), the positive electrode material is any one of lithium iron phosphate, lithium iron manganese phosphate, NCM622 and NCM811; the negative electrode material is any one of graphite, lithium titanate, silicon carbon, silicon oxygen and hard carbon.
[0017] Furthermore, in step (1), the conductive agent is at least two of Ketjen black, carbon nanotubes, Super P and vapor-grown carbon fibers.
[0018] Furthermore, in step (1), the main binder is PTFE, and the additive is at least one of polymers such as polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polyvinyl pyrrolidone (PVP) and polyaniline (PANI).
[0019] Furthermore, the lithium salt in the electrolyte is one of LiTFSI and LiPF6, and the solvent is at least one of PC, EC, EMC, DEC, and DMC.
[0020] Furthermore, when the fiberized positive and negative electrode materials are kneaded with the electrolyte in step (2), the electrolyte needs to completely soak the materials.
[0021] Furthermore, the amount of electrolyte used in step (2) should be no less than 20wt% of the total solid-liquid mass, preferably between 30wt% and 40wt%. The total solid-liquid mass refers to the total mass of the positive electrode active material and the electrolyte or the total mass of the negative electrode active material and the electrolyte.
[0022] Furthermore, in step (3), the positive electrode current collector is a carbon-coated aluminum foil, and the thickness of the carbon coating layer is 2 μm.
[0023] Furthermore, in step (3), the mixture is kneaded and rolled, and the roll gap width is gradually reduced during rolling, with each reduction not exceeding 100 μm, until the desired thickness is reached. The thickness can be designed to be between 100 μm and 600 μm, and the electrolyte does not precipitate during the rolling process.
[0024] Furthermore, during the rolling process in step (3) and step (4), the temperature is 20°C-25°C, and the pressure is between 0.1T-2T.
[0025] Furthermore, the negative electrode current collector in step (4) is carbon-coated aluminum foil or carbon-coated copper foil.
[0026] Furthermore, in step (5), the material of the isolation layer is at least one of polypropylene PP, polyethylene PE, polyethylene terephthalate PET, and ethyl methyl carbonate EMC.
[0027] Furthermore, steps (2) to (5) are all performed within a dew point temperature range of -35°C to 45°C.
[0028] The present invention has the following beneficial effects: during the mixing process, the fiber filaments obtained by fibrillating the binder PTFE can connect the positive and negative active materials and the conductive agent to construct a complete electrode structure; the conductive network constructed by the mixed conductive agent can improve the cycle performance of the battery, and the addition of polymer additives can significantly improve the adhesion between the current collector and the semi-solid pole piece. The semi-solid lithium battery described in the present application is different from the existing semi-solid battery with in-situ solidification of the electrolyte, and does not have the problem of uneven electrolyte distribution. It is also different from the traditional lithium-ion battery preparation process, reducing the steps of homogenization, coating, etc., and reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 These are SEM images of the positive electrode fiberized materials obtained in Example 1 and Comparative Example 1, wherein (a) is the SEM image of the positive electrode fiberized material in Example 1; (b) is the SEM image of the positive electrode fiberized material in Comparative Example 1.
[0031] Figure 2 The charge and discharge curves of the assembled batteries of Example 1 and Comparative Examples 1-2 are shown.
[0032] Figure 3 It is a cycle performance diagram of the assembled batteries of Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0034] Example 1
[0035] The preparation method of the semi-solid lithium battery of this embodiment is as follows:
[0036] (1) The positive electrode active material lithium iron phosphate, the conductive agent SP and KB, the binder PTFE, and the additive PEO were mixed in a mass ratio of 95:2.1:0.9:1.5:0.5, and a double planetary mixer was used for high-speed shearing fiberization. The materials were mixed at 1200 rpm for 5 minutes and at 1800 rpm for 5 minutes. The materials were mixed three times to obtain the positive electrode fiberized material and kept at 50°C for 6 hours; the negative electrode active material lithium titanate, the conductive agent SP and KB, the binder PTFE, and the additive PEO were mixed in a mass ratio of 95:2.1:0.9:1.5:0.5, and a double planetary mixer was used for high-speed shearing fiberization. The materials were mixed at 1200 rpm for 5 minutes and at 1800 rpm for 5 minutes. The materials were mixed three times to obtain the negative electrode fiberized material and kept at 50°C for 6 hours. PEO can increase the viscosity between the current collector and the semi-solid electrode.
[0037] (2) Add 40wt% (the mass of the positive electrode fiberized material accounts for 60wt%) of the electrolyte after the positive electrode fiberization, and mix them into uniform spheres in a degassing machine. Add 30wt% (the mass of the negative electrode fiberized material accounts for 70wt%) of the electrolyte after the negative electrode fiberization material, and mix them into uniform blocks in a degassing machine. The lithium salt in the electrolyte is 0.5M LiTFSI and the solvent is PC.
[0038] (3) Place the semi-solid slurry of the positive electrode in a PP separator and roll it using a double-roller. During the rolling process, the temperature is 25°C and the pressure is between 0.5-1.5T. Roll it multiple times to reduce the thickness to 200μm. Roll the cut carbon-coated aluminum foil and the electrode sheet together. Roll the negative electrode material to 200μm and composite it with the carbon-coated copper foil.
[0039] (4) The prepared positive and negative electrodes were cut into 12 mm diameter discs for later use, assembled and charged (N / P ratio was 1.13), and the battery performance was tested.
[0040] Example 2
[0041] The preparation method of the semi-solid lithium battery of this embodiment is as follows:
[0042] (1) The positive electrode active material NCM811, the conductive agent SP and KB, the binder PTFE, and the additive PEO were mixed in a mass ratio of 95:2.1:0.9:1.5:0.5 using a double planetary mixer, first stirred at a low speed of 1000 rpm for 10 minutes, then stirred at a high speed of 1600 rpm for 10 minutes, and repeated three times. The total mixing time was 60 minutes to obtain the positive electrode fiberized material and keep it at 50°C for 6 hours. The negative electrode active material graphite, the conductive agent SP and KB, the binder PTFE and the additive PEO were mixed in a mass ratio of 95:2.1:0.9:1.5:0.5. The negative electrode mixing method was the same as the positive electrode mixing method to obtain the negative electrode fiberized material and keep it at 50°C for 6 hours.
[0043] (2) 40 wt% electrolyte was added to the sample after positive electrode fiberization, and 30 wt% electrolyte was added to the sample after negative electrode fiberization to mix into uniform blocks. Both were prepared in a degassing machine. The lithium salt in the electrolyte was 0.5 M LiTFSI and the solvent was PC.
[0044] (3) The semi-solid slurry of the positive electrode is placed in a PP separator and rolled using a flat roller. The temperature during the rolling process is 25°C and the pressure is between 0.5-1.5T. The slurry is thinned to 300μm by multiple rolling. The cut carbon-coated aluminum foil is rolled together with the electrode. The negative electrode material is also rolled to 280μm and composited with the carbon-coated copper foil.
[0045] (4) The prepared positive and negative electrodes were cut into 12 mm diameter discs for later use, assembled and charged (N / P ratio was 1.17), and the battery performance was tested.
[0046] Example 3
[0047] The preparation method of the semi-solid lithium battery of this embodiment is as follows:
[0048] (1) The positive electrode active material NCM622, the conductive agent SP and KB, and the binder PTFE were mixed in a mass ratio of 95:2.1:0.9:2 using a double planetary mixer, first stirred at a low speed of 1100 rpm for 8 minutes, then stirred at a high speed of 2000 rpm for 8 minutes, and repeated three times to obtain the positive electrode fiberized material and keep it at 50°C for 6 hours. The negative electrode active material graphite, the conductive agent SP and KB, the binder PTFE, and the additive PAA were mixed in a mass ratio of 95:2.1:0.9:1.5:0.5. The negative electrode mixing method was the same as the positive electrode mixing method to obtain the negative electrode fiberized material and keep it at 50°C for 6 hours.
[0049] (2) Add 30 wt% of electrolyte to the sample after positive electrode fiberization and mix evenly into spheres, and add 40 wt% of electrolyte to the sample after negative electrode fiberization and mix into uniform blocks, both of which are prepared in a degassing machine.
[0050] (3) The semi-solid slurry of the positive electrode is placed in a PP separator and rolled using a flat roller. The temperature during the rolling process is 25°C and the pressure is between 0.5-1.5T. The slurry is thinned to 300μm by multiple rolling. The cut carbon-coated aluminum foil is rolled together with the electrode. The negative electrode material is also rolled to 270μm and composited with the carbon-coated copper foil.
[0051] (4) The prepared positive and negative electrodes were cut into 12 mm diameter discs for later use. The lithium salt in the electrolyte was 0.5 M LiTFSI, the solvent was PC, and the battery was assembled and charged (N / P ratio was 1.07) to test the battery performance.
[0052] Example 4
[0053] The positive electrode active material in Example 1 was adjusted to lithium manganese iron phosphate, the amount ratio remained unchanged, and the fibrous positive and negative electrode materials were obtained by mixing, and the subsequent processes remained the same.
[0054] Comparative Example 1
[0055] On the basis of Example 1, without adding PEO additive, the specific preparation method is as follows:
[0056] (1) The positive electrode active material lithium iron phosphate, the conductive agents SP and KB, and the binder PTFE were mixed in a mass ratio of 95:2.1:0.9:2; the negative electrode active material lithium titanate, the conductive agents SP and KB, and the binder PTFE were mixed in a mass ratio of 95:2.1:0.9:2. The positive and negative electrode mixing methods were consistent with those in Experimental Example 1.
[0057] (2) Add 40 wt% electrolyte to the sample after positive electrode fiberization and mix evenly into spheres, and add 30 wt% electrolyte to the sample after negative electrode fiberization and mix evenly. Both are prepared in a degassing machine. The lithium salt in the electrolyte is 0.5 M LiTFSI and the solvent is PC.
[0058] (3) The semi-solid slurry of the positive electrode in a lump is placed in a PP separator and rolled using a flat roller machine. During the rolling process, the temperature is 25°C and the pressure is between 0.5-1.5T. The slurry is thinned to 200 μm by multiple rolling. The cut carbon-coated aluminum foil is rolled together with the electrode sheet; the negative electrode material is also rolled to 200 μm and composited with the carbon-coated copper foil.
[0059] (4) The prepared positive and negative electrodes were cut into 12 mm diameter discs for later use, assembled and charged (N / P ratio was 1.13), and the battery performance was tested.
[0060] Comparative Example 2
[0061] The conductive agent in Example 1 was changed to SP, the mass ratio remained unchanged, and the mixed materials were obtained to obtain fibrous positive and negative electrode materials. The subsequent processes were consistent with Example 1.
[0062] Comparative Example 3
[0063] The conductive agent in Example 1 was changed to KB, the mass ratio remained unchanged, and the mixed materials were obtained to obtain fibrous positive and negative electrode materials. The subsequent processes were consistent with Example 1.
[0064] The semi-solid-state battery prepared above was subjected to cycle testing to compare its electrical performance. The battery cycle testing method is: charging and discharging at a rate of 0.1C under the conditions of a temperature of 25°C and a charge and discharge voltage of 2.5-4.2V.
[0065] Table 1 Battery charge and discharge test data
[0066]
[0067] It can be seen from the data in Table 1 that the batteries have good charge and discharge performance by using different positive and negative electrode materials, and can be applied to lithium batteries of different systems; it can be seen from the test data of Example 1 and Comparative Example 1 that after adding PEO, the first efficiency of the whole battery is improved to 92.6%, and the capacity is also better than that of Comparative Example 1. This is because the adhesion between the current collector and the electrode is improved by the addition of PEO; comparing the charge and discharge data of Example 1 and Comparative Examples 2 and 3, the first efficiency and capacity of the mixed conductive agent are higher than those of the single conductive agent type.
[0068] The positive and negative electrode materials after fiberization in Example 1 and Comparative Example 1 were respectively subjected to scanning electron microscopy testing, and the SEM images thereof are as follows: Figure 1 As shown. Figure 1 It can be seen that the conductive agent is distributed on the surface of LFP, and there are certain gaps between the materials, which provides space for the subsequent electrolyte and allows for more complete infiltration. The morphology does not change after the addition of PEO.
[0069] Comparing Example 1 and Comparative Example 1, the electrochemical performance of Comparative Example 2 is as follows Figure 2 , Figure 3 As shown. Figure 2 From the charge and discharge curves, it can be seen that the polarization voltage of Example 1 is also lower than that of Comparative Example 1, and the capacity performance is also better than that of Example 1. Figure 3 It can be seen that the cycle performance of the whole battery is better after adding PEO. This is because the addition of PEO improves the adhesion between the current collector and the electrode, which alleviates the electrode shedding caused by electrolyte consumption during charging and discharging. The cycle performance of the mixed conductive agent is better than that of a single conductive agent. This is because the conductive network constructed by the mixed conductive agent increases the wettability of the electrolyte to the fiberized material.
[0070] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a semi-solid lithium battery, characterized in that: PTFE fibrillation connects active materials and binary conductive agents to construct electrode structures, and the electrolyte is evenly distributed, and ultra-thick electrodes can be designed, including the following steps: (1) The positive and negative electrode active materials are mixed with a conductive agent, a binder, and an additive in a certain proportion, and the positive and negative electrode materials are prepared by high-speed shearing to form fiberized positive and negative electrode materials, and then kept warm at a specific temperature; (2) adding electrolyte to the heat-insulated positive electrode active material and mixing, and preparing wet small balls or dough in a degassing machine to obtain a wet positive electrode mixture; adding electrolyte to the heat-insulated negative electrode active material and mixing, and preparing wet small balls or dough in a degassing machine to obtain a wet negative electrode mixture; (3) Placing the wet positive electrode mixture in the separator and applying pressure to reduce it to the designed thickness, and rolling it with the current collector to obtain a positive electrode semi-solid electrode sheet; (4) placing the wet negative electrode mixture in the separator and applying pressure to reduce it to the designed thickness, and rolling it with the current collector to obtain a negative electrode semi-solid electrode sheet; (5) Assemble the positive and negative semi-solid electrodes into a lithium battery and conduct a static test.
2. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: The positive electrode active material in step (1) is any one of lithium iron phosphate, lithium iron manganese phosphate, NCM622 and NCM811; the negative electrode active material is any one of graphite, lithium titanate, silicon carbon, silicon oxygen and hard carbon.
3. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: The conductive agent is at least two of Ketjen Black KB, carbon nanotubes, Super P and vapor-grown carbon fibers.
4. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: The binder in step (1) is polytetrafluoroethylene (PTFE) with a purity of 99.9% and a molecular weight of 10 5 -10 8 g / mol, and the additive is at least one of polyethylene oxide PEO, polyvinylidene fluoride PVDF, polyacrylic acid PAA, polyvinyl pyrrolidone PVP and polyaniline PANI.
5. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: In the step (1), the mass ratio of the positive electrode active material to the conductive agent, the binder, and the additive is 95:3:1.5:0.5, and the mass ratio of the negative electrode active material to the conductive agent, the binder, and the additive is 95:3:1.5:0.
5. The temperature during the mixing process is 25-30°C.
6. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: In the step (1), high-speed shearing is performed using a double planetary mixer, and stirring is performed at a speed of 1000-2000 rpm for 30 min-60 min to perform high-speed shearing fiberization; the sample after fiberization is in a granular state, and the temperature range of the insulation is between 40-100°C.
7. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: The amount of electrolyte added in step (2) is 30 wt%-40 wt% of the total mass of solid and liquid, and the mixed material is in a ball or dough shape.
8. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: The isolation layer in steps (3) and (4) is at least one of polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), and ethyl methyl carbonate (EMC).
9. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: The pressure applied in steps (3) and (4) is in the range of 0.1T-2T. The thickness of the electrode sheet is adjusted by adjusting the roller gap width to prepare positive and negative electrode sheets with a thickness of 100µm-600µm.
10. The method for preparing a semi-solid lithium battery according to claim 1, characterized in that: During the operation of steps (2) to (5), the temperature is controlled between 20°C and 25°C, and the dew point temperature is between -35°C and 45°C.
Citation Information
Cited By
Binder, negative electrode and battery
CN121293915A
